Adolescents from Broken Homes: The Role of Emotional Regulation in Reducing Aggressive Tendencies - Yohana Eronika Antikaningsih; Dewita Karema Sarajar (Jurnal Bimbingan dan Konseling Terapan)
Adolescence, spanning ages 10 to 21, is a critical stage of human development marked by significant biological, emotional, and psychosocial changes. This study explores the relationship between emotional regulation and aggression among adolescents from broken homes—familial structures disrupted by parental separation or divorce. Utilizing a quantitative correlational design, the study engaged 171 adolescents aged 13–22 years from diverse regions in Indonesia. Data collection involved validated Emotional Regulation and Aggressive Behavior Scales administered through online platforms. Findings revealed a significant inverse relationship between emotional regulation and aggression (r = -0.560, p < 0.001), with higher emotional regulation correlating with lower aggression levels. Most participants exhibited moderate emotional regulation and aggression, indicating the capacity to manage emotions in typical situations but vulnerability to reactive aggression under stress. Emotional regulation emerged as a protective factor against the adverse effects of familial instability, mitigating aggressive tendencies and fostering adaptive behaviors. The study emphasizes the importance of targeted counseling interventions, including mindfulness, cognitive-behavioral therapy, and family counseling, to enhance emotional regulation and reduce aggression in this vulnerable population. Limitations include reliance on quantitative methods, suggesting the need for mixed-methods research to capture nuanced emotional experiences and contextual factors such as peer influence and socioeconomic conditions. These findings underscore the pivotal role of emotional regulation in adolescent development, providing insights for educators, counselors, and policymakers to support the well-being of adolescents from broken homes.